The Model of Environment Gradation: Environment Awareness Mediates Low Society Economic, Negative Attitude, and Community Culture - M. Havidz Aima; Ridwansyah (Jujurnal Publisher, 2024)
This article develops and qualitatively examines a conceptual model of environment gradation—defined as patterned differences in environmental quality, resilience, and stewardship across neighborhoods and communities—by theorizing how environmental awareness mediates three antecedent conditions: low socioeconomic circumstances (hereafter “low society economic”), negative environmental attitudes, and community culture. We synthesize recent literature (last five years) and present an interpretive, multi-site qualitative design to illuminate mechanisms through which awareness translates structural disadvantage and cultural scripts into situated practices. The study integrates perspectives from value–belief–norm (VBN) theory, social cognitive theory, and environmental justice scholarship to explain when and how awareness facilitates (or fails to facilitate) pro-environmental behavior under constraint. A comparative thematic analysis, supported by interviews, focus groups, walk-along observations, and document review, identifies four cross-cutting pathways—knowledge gaps, risk salience, social identity and norms, and structural friction—through which environmental awareness either amplifies or buffers the effects of economic precarity, apathy/fatalism, and local cultural logics. We contribute: (1) a definition and operationalization of environment gradation at community scale; (2) a mediated model that clarifies the role of awareness amid resource scarcity; and (3) actionable implications for municipal programs that combine economic relief, culturally grounded communication, and community-led stewardship. We conclude with a 15-study synthesis table (2019–2025) and recommendations for future mixed-methods testing of the proposed pathways.